2016
DOI: 10.1332/030557314x13904856745154
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising the active welfare subject: welfare reform in discourse, policy and lived experience

Abstract: The idea of the active welfare subject has become irresistible to both policy makers and academics and has taken a lead role in the transformation of twenty-first century social security systems. Two distinguishable approaches have emerged – the dominant model and a counter model. The dominant model emphasises moralised individual responsibility for ‘wrong choices’ and mandates behavioural change to become active. The counter model situates benefit recipients in the present as disempowered creative, reflexive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 15 publications
2
129
0
2
Order By: Relevance
“…Despite the overtly moralistic tone of political discourse surrounding behavioral welfare reform (Garthwaite, 2011;Jensen & Tyler, 2015;Patrick, 2016;Wiggan, 2012), the meaning and import of behavioral conditionality for street-level practice have received less attention. Given that the individualized, moralized, and coercive character of welfare conditionality is often central to citizens' experiences of welfare reform (Flint, 2019;Friedli & Stearn, 2015;Garthwaite, 2014;Patrick, 2017;Reeve, 2017;Wright, 2016), it is important to understand the role of street-level practitioners in producing these relations and experiences.…”
mentioning
confidence: 99%
“…Despite the overtly moralistic tone of political discourse surrounding behavioral welfare reform (Garthwaite, 2011;Jensen & Tyler, 2015;Patrick, 2016;Wiggan, 2012), the meaning and import of behavioral conditionality for street-level practice have received less attention. Given that the individualized, moralized, and coercive character of welfare conditionality is often central to citizens' experiences of welfare reform (Flint, 2019;Friedli & Stearn, 2015;Garthwaite, 2014;Patrick, 2017;Reeve, 2017;Wright, 2016), it is important to understand the role of street-level practitioners in producing these relations and experiences.…”
mentioning
confidence: 99%
“…As a result, there is hardly any chance to realize one’s own autonomy claims, such as social autonomy, professional self‐realization or moral autonomy (i.e., notions of excellence). This autonomy conflict hints at the “disempowering context of ‘Othering’” (Wright, , p. 239), which increases the social distance between those who are in a position to play the game and those on the sidelines.…”
Section: Autonomy Revisited—empirical Approach and Resultsmentioning
confidence: 99%
“…These portrayals were also present in this study, were unemployed citizens felt they were treated with constant suspicion and viewed as incompetent. These portrayals lie on the core assumption that unemployment is caused by lack of will to take responsibility for one's own life, hence the need for activation programs and incentives (Wright 2016). However, if we move from the unemployed assumed capabilities, to actual capabilities on the ground, we notice that these are rather complex and limited, as all citizens in this study suffer from health-related issues in addition to unemployment.…”
Section: Myriad Of Assumptions Leading To Incongruence Framesmentioning
confidence: 89%
“…However, an overlooked aspect is how these reforms look when enacted in practice (Lødemal & Trickey 2001). A large part of the literature about public welfare focuses on the discursive tactics used in policy and welfare programs (Christensen 200;Turgeon et al 2014;Wright 2016), but the topic of assumptions inscribed in welfare policies and tools, and their impact on local practices remain relatively underexplored. 1 Previously, I found that the tools used by caseworkers are designed to ensure policy compliance, while providing limited support for caseworkers helping citizens obtain an employment (Boulus-Røde 2018).…”
Section: Public Policy and Social Welfarementioning
confidence: 99%
See 1 more Smart Citation